Input performance limitations of feedback control - Meadows, Edward S. (2009)
This paper deals with input performance limitations of feedback control. The achievable input performance depends on the joint controllability and observability of unstable poles and is exactly quantified for single input single output (SISO) and multi input multi output (MIMO) systems with and without time delay. We also present a modification of u-interaction measure to assess the feasibility of decentralized stabilization with independent designs of loops. The results are useful for various purposes including designs of the process, control structure and optimal controller synthesis.